RETRACTED: THE STABILITY OF GAUSS MODEL HAVING ONEPREY TWO-PREDATORS - Farajzadeh, A.; Doust, M. H. R.; Haghighifar, F. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
Scientists are interesting to find conditions to continuously use of living resourcesat the same time. In the present paper, some Gauss predatorpreymodels in whichtree ecologically interacting species has been considered and the behavior of their solutionsin the stability aspect have been investigated. The main aim is to present a mathematicalanalysis for the above models as global and local stability. Finally, stability of some examplesof Gauss model with two preys and on predator are discussed